Active integrated antenna with simultaneous transmit and receive - 264106 Xuefeng, Qi; Mohamad Kamal A. Rahim (2007)
Thesis (Sarjana Kejuruteraan (Elektrikal - Elektronik dan Telekomunikasi )) - Universiti Teknologi Malaysia, 2007